2021
DOI: 10.3389/fmicb.2020.586476
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia muciniphila Improves Host Defense Against Influenza Virus Infection

Abstract: Influenza virus infection can alter the composition of the gut microbiota, while its pathogenicity can, in turn, be highly influenced by the gut microbiota. However, the details underlying these associations remain to be determined. The H7N9 influenza virus is an emerging zoonotic pathogen which has caused the death of 616 humans and has incurred huge losses in the poultry industry. Here, we investigated the effects of infection with highly pathogenic H7N9 on gut microbiota and determined potential anti-influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 51 publications
4
35
0
Order By: Relevance
“…While challenged with the same dose, this mouse showed reduced clinical signs throughout infection, thus suggesting that the decreased abundance of Akkermansia in this mouse could be correlated to disease severity. A recent report showed that while the abundance of Akkermansia positively correlated with influenza H7N9 infection in mice, oral administration of A. muciniphila significantly reduced weight loss, mortality, and viral titers ( 22 ). Therefore, further research is needed to better understand the role of Akkermansia in severe SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While challenged with the same dose, this mouse showed reduced clinical signs throughout infection, thus suggesting that the decreased abundance of Akkermansia in this mouse could be correlated to disease severity. A recent report showed that while the abundance of Akkermansia positively correlated with influenza H7N9 infection in mice, oral administration of A. muciniphila significantly reduced weight loss, mortality, and viral titers ( 22 ). Therefore, further research is needed to better understand the role of Akkermansia in severe SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Reported changes in the intestinal microbiome include enrichment of Bacteroides and Proteobacteria along with a decrease in Firmicutes during respiratory viral infections such as influenza virus and respiratory syncytial virus (RSV) ( 18 21 ). Not only were changes observed in the intestinal bacterial communities, but it was demonstrated that TLR5 sensing of flagellated microbes in the intestine increased antibody responses post-influenza virus vaccination and that the oral administration of gut microbe Akkermansia muciniphila reduced weight loss and mortality during highly pathogenic influenza virus infection ( 22 , 23 ). It has also been suggested that microbiome changes or “gut dysbiosis” can lead to gut permeability, resulting in secondary infections such as pneumococcal disease ( 20 , 21 ).…”
mentioning
confidence: 99%
“…Interestingly, increased abundances of this species were detected in multiple sclerosis patients [12][13][14]31] and were implicated in the increased susceptibility towards enteropathogenic infections in the same 14SM mouse model as used in this study [6]. However, other studies report on strong host-beneficial effects of this species [17,32], in some cases classifying A. muciniphila as "probiotic" [33]. These findings, which appear contradictory at first, might be rooted in different microbiome-mediated mechanisms of disease pathology, the considerable diversity among different commensal A. muciniphila strains [34] or in the complex inter-microbial influences within a given microbiome, which we observe even in a reduced community of only 14 strains.…”
Section: Discussionmentioning
confidence: 60%
“…Additionally, oral administration of this bacterium still inhibited H7N9 proliferation and improved clinical symptoms [62]. Thus, the endogenous increase of Akkermansia muciniphil in COVID-19 may be harmless.…”
Section: Moreover It Was Metabolically Complementary To Butyrate-producing Bacteriummentioning
confidence: 97%
“…The anti-inflammatory effect of Akkermansia muciniphila depends on the outer membrane protein Amuc_1100 [72]. Such a result may partially explain why the increased abundance of Akkermansia muciniphila did not endogenously alleviate COVID-19 and H7N9 progressions [62]. Clostridium leptum was reduced in the COVID-19 group, and its low metabolic activity further impeded its positive effect on disease progression.…”
Section: Salmonella Infection Pertussis and Bacterial Invasion Of Epithelial Cells) Indicated The Human Gut Is The Site Of Extrapulmonarymentioning
confidence: 99%